A "step too far" or "perfect sense"? A qualitative study of British adults' views on mandating COVID-19 vaccination and vaccine passports. Issue 51 (5th December 2022) - Stead, Martine; Ford, Allison; Eadie, Douglas; Biggs, Hannah; Elliott, Claire; Ussher, Michael; Bedford, Helen; Angus, Kathryn; Hunt, Kate; MacKintosh, Anne Marie; Jessop, Curtis; MacGregor, Andy
Abstract: Background: Debate is ongoing about mandating COVID-19 vaccination to maximise uptake. Policymakers must consider whether to mandate, for how long, and in which contexts, taking into account not only legal and ethical questions but also public opinion. Implementing mandates among populations who oppose them could be counterproductive. Methods: Qualitative telephone interviews (Feb-May 2021) with British adults explored views on vaccine passports and mandatory vaccination. Participants (n = 50) were purposively selected from respondents to a probability-based national survey of attitudes to COVID-19 vaccination, to include those expressing vaccine-hesitancy. Data were analysed thematically. Findings: Six themes were identified in participants' narratives concerning mandates: (i) mandates are a necessary and proportionate response for some occupations to protect the vulnerable and facilitate the resumption of free movement; (ii) mandates undermine autonomy and choice; (iii) mandates represent an over-reach of state power; (iv) mandates could potentially create 'vaccine apartheid'; (v) the importance of context and framing; and (vi) mandates present considerable feasibility challenges. Those refusing vaccination tended to argue strongly against mandates. However, those in favour of vaccination also expressed concerns about freedom of choice, state coercion and social divisiveness. Discussion: To our knowledge, this is the first in-depth UK study of public views on COVID-19 vaccine mandates. It does not assess support for different mandates but explores emotions, principles and reasoning underpinning views. Our data suggest that debate around mandates can arouse strong concerns and could entrench scepticism. Policymakers should proceed with caution. While surveys can provide snapshots of opinion on mandates, views are complex and further consultation is needed regarding specific scenarios.